Metallized film for capacitor, preparation method thereof and capacitor
By preparing inorganic reinforcement materials and modified polypropylene base films, applying polyester coating on the base film and irradiation treatment, finally forming a metal layer through vacuum evaporation, the thermal stability and mechanical properties of the polypropylene film are solved. The problem is that a high-performance metallized film for capacitors is realized.
Patent Information
- Application Number
- CN202411588814.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-08
AI Technical Summary
In the prior art, the thermal stability and mechanical properties of the polypropylene film are insufficient, making it difficult to maintain good performance in a high temperature environment.
Inorganic reinforcement materials are prepared using raw materials including 1,4-phthalaldehyde, zirconium diboride, and ethyl orthosilicate, and a modified polypropylene-based film is obtained by melt kneading, casting sheet molding and bidirectional stretching. A polyester coating is applied to the base film and an electron beam and ultraviolet light source irradiation treatment is performed, and a metal layer is finally formed by vacuum evaporation to obtain a metallized film.
The thermal stability and mechanical properties of the polypropylene film are significantly improved, the material has excellent heat resistance, excellent mechanical properties, and the inorganic reinforced materials are uniformly and stably dispersed, avoiding agglomeration.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of capacitor manufacturing, and in particular to a metallized film for a capacitor, a preparation method thereof, and a capacitor. Background Art
[0002] Metallized film is a thin film material with unique properties. It has the characteristics of high square resistance, good oxidation resistance, self-healing and easy processing, so it has important application value in many fields. The base film of the metallized film can be a polymer material such as polyester and polypropylene, and one or more layers of metal are plated on the base film to form a thin film material with a certain square resistance value. The metal coating can be a metal or alloy such as aluminum, zinc, zinc-aluminum alloy, etc.
[0003] As a basic electronic component, capacitors are widely used and exist in almost all electronic products. The dry-type power frequency resonance system is an electronic device that uses the relationship between the tuning inductor and the load capacitance to generate series resonance under power frequency conditions to obtain the required power frequency test voltage. As an important power equipment, the dry-type power frequency resonance system is mainly used for the handover and preventive testing of high-voltage capacitive test products to ensure the stable operation of the power system.
[0004] "Square resistance" refers to the resistance of a plane conductor per unit square, and is an important parameter of metallized film. The reason why metallized film has the characteristic of high square resistance is that the resistance value of its metal coating is relatively high. This is usually caused by a thin metal coating or a low conductivity of the metal material. The high square resistance characteristic of the metallized film means that it will generate a larger voltage under the same current. Therefore, the metallized film has unique performance advantages and broad application prospects in dry power frequency resonance systems.
[0005] Polypropylene film has the advantages of small specific gravity, stable chemical properties, low cost, mature technology, etc., and it can maintain a small dielectric thickness and good dielectric strength under the working voltage of high-voltage capacitors. Therefore, polypropylene film has become a base film material with great application prospects in the field of capacitors, especially in the field of high-voltage capacitors such as dry-type industrial frequency resonance systems.
[0006] The shortcomings of polypropylene film are that its thermal stability is not ideal, and its mechanical properties (especially tensile strength) also have a certain room for improvement. The methods of improving the performance of polypropylene film in the prior art mainly include adding polymer materials for modification and adding inorganic reinforcing materials for modification. Among them, polyimide materials have excellent high temperature resistance, excellent mechanical properties, and high electrical insulation properties, so they can be used to modify polypropylene. There are many types of inorganic reinforcing materials that can be used to modify polypropylene, such as silicon oxide, aluminum oxide, zirconium oxide, silicon carbide, silicon nitride and other inorganic non-metallic powders, which can enhance the mechanical properties and mechanical properties of polypropylene.
[0007] For example, the prior art with the authorization announcement number CN118271780B provides a biaxially synchronously stretched polypropylene film material, which includes polypropylene modified by irradiation grafting, polyetherimide reinforced fiber, nano zirconium boride and reaction aid. The polypropylene film material is obtained by melt mixing and extrusion of the above raw materials to obtain a sheet fluid; then it is formed by chilled rollers and high-pressure air knife casting to obtain a membrane; finally, it is stretched longitudinally and transversely by a mechanical stretching machine, and is obtained after shaping and cooling. Among them, polyetherimide and nano zirconium boride can improve the high temperature resistance and mechanical strength of the polypropylene film material.
[0008] It is known to those skilled in the art that inorganic nanopowders such as zirconium boride have high surface energy and are difficult to disperse uniformly in polymers, and are easily agglomerated during melt mixing. The above prior art improves the interface properties between polypropylene and polyetherimide modifiers and nano zirconium boride modifiers by using triallyl phosphate irradiation grafting technology.
[0009] However, the above technical solution still has the disadvantage that the triallyl phosphate irradiation grafting technology can only improve the interface performance of polypropylene materials by adjusting the side chain structure, and it is still difficult to achieve the modification of zirconium boride and the organic connection between zirconium boride and polypropylene and / or polyetherimide, which leads to the interface adhesion between zirconium boride and polypropylene and / or polyetherimide still needs to be improved. Accordingly, the high temperature resistance and mechanical properties of polypropylene-based films in the prior art also have a certain room for improvement. Summary of the invention
[0010] One of the problems solved by the present invention is how to provide a metallized film for capacitors with excellent thermal stability and mechanical properties.
[0011] In order to solve at least one of the above problems, the present invention provides a method for preparing a metallized film for a capacitor, the preparation method comprising:
[0012] S100, preparing an inorganic reinforcing material using raw materials including 1,4-phthalaldehyde, zirconium diboride, and ethyl orthosilicate;
[0013] S200, preparing a modified polypropylene material using raw materials including 4,4'-diaminobiphenyl, triphenyl phosphate, ethylene-1-octene copolymer, polyethylene, and polypropylene;
[0014] S300, melt-mixing, casting and biaxially stretching raw materials including polyvinyl alcohol, silane coupling agent, N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, inorganic reinforcing material and modified polypropylene material to obtain a base film;
[0015] S400, applying a polyester coating on the base film, and irradiating the base film with an electron beam and an ultraviolet light source in sequence to obtain a modified base film;
[0016] S500, forming a metal layer by vacuum evaporation on the side of the modified base film having the polyester coating to obtain a metallized film.
[0017] In the above technical solution, S100 specifically includes:
[0018] S110, dissolving 1,4-benzenedicaldehyde in ethanol at a mass ratio of 1,4-benzenedicaldehyde: zirconium diboride: ethyl orthosilicate: water: ethanol = (2-6): (10-20): (30-50): (30-50): 100, and then adding zirconium diboride, ethyl orthosilicate and water and mixing them evenly to obtain a first mixture;
[0019] S120, adjusting the pH value of the first mixture to 4 to 5 by dropwise adding aqueous hydrochloric acid solution and stirring, and continuing stirring for 2 h to 2.5 h to obtain silica sol;
[0020] S130, placing the silica sol in anhydrous ethanol and soaking it at a temperature of 50° C. to 55° C. for 30 to 36 hours to obtain a silica gel;
[0021] S140, drying the silicone gel at a temperature of 100° C. to 120° C. under normal pressure, and grinding the silica gel into powder to obtain an inorganic reinforcing material.
[0022] In the above technical solution, S200 specifically includes:
[0023] S210, weighing and mixing 4,4'-diaminobiphenyl, triphenyl phosphate, ethylene-1-octene copolymer, polyethylene and polypropylene in a mass ratio of 4,4'-diaminobiphenyl:triphenyl phosphate:ethylene-1-octene copolymer:polyethylene:polypropylene=(2-6):(2-6):(4-8):(10-20):100 to obtain a second mixture;
[0024] S220, sending the second mixture into an internal mixer, mixing at a temperature of 150° C. to 160° C. for 20 min to 40 min, discharging, cooling, and pelletizing to obtain a modified polypropylene material;
[0025] Among them, the weight average molecular weight of polyethylene is 200,000 to 300,000, and the weight average molecular weight of polypropylene is 200,000 to 250,000.
[0026] In the above technical solution, S300 specifically includes:
[0027] S310, weighing and mixing polyvinyl alcohol, silane coupling agent, N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, inorganic reinforcing material and modified polypropylene material according to a mass ratio of polyvinyl alcohol: silane coupling agent: N-hydroxynaphthaleneimide trifluoromethanesulfonic acid: inorganic reinforcing material: modified polypropylene material = (1-2): (2-4): (2-4): (10-15): 100 to obtain a third mixture;
[0028] S320, feeding the third mixture into a twin-screw extruder, and extruding the mixture after melt-mixing at a temperature of 170° C. to 190° C. to obtain a sheet-like fluid;
[0029] S330, casting the sheet-like fluid through a chilled roller at 80° C. to 100° C. and a high-pressure air knife to obtain a membrane;
[0030] S340, stretch the film in the longitudinal direction at a stretching ratio of 4 to 5 times and in the transverse direction at a stretching ratio of 5 to 6 times on a mechanical stretching machine at a temperature of 125°C to 145°C, and heat-set at a temperature of 150°C to 160°C to obtain a base film.
[0031] In any of the above technical solutions, S400 includes:
[0032] S410, feeding butanediol and ethylene terephthalate into a vacuum reactor in a mass ratio of titanium dioxide: zinc acetate: butanediol: ethylene terephthalate = (1-2): (4-6): (50-60): 100, reacting at a temperature of 180° C. to 190° C. for 60 min to 100 min, adding titanium dioxide and zinc acetate, raising the temperature to 220° C. to 250° C. and continuing the reaction for 40 min to 60 min to obtain polyester;
[0033] S420, mixing polyester and carbon tetrachloride in a mass ratio of polyester: carbon tetrachloride = (20-30): 100, and heating to 65° C. to 70° C. to obtain a polyester coating;
[0034] S430, applying the polyester coating on the base film at a mass ratio of polyester coating: base film = (2-4): 100, and heating and drying to evaporate and remove carbon tetrachloride;
[0035] S440, successively irradiating the base film with an electron beam and then with an ultraviolet light source to obtain a modified base film.
[0036] In the above technical solution, in S440, the radiation dose of the electron beam irradiation treatment is 20kGy-30kGy, and the exposure dose of the ultraviolet light source irradiation treatment is 1000mJ / cm 2 Up to 1200mJ / cm 2 .
[0037] In any of the above technical solutions, in S500, the vacuum evaporation conditions include: the evaporation material is aluminum, the vacuum degree is 2×10 -5 Pa or less, the evaporation rate is 0.02A / s to 0.08A / s, the evaporation time is 60s to 180s, and the substrate temperature is 140°C to 150°C.
[0038] In any of the above technical solutions, the thickness of the modified base film is 5 μm to 20 μm, and the thickness of the metal layer is 5 nm to 50 nm.
[0039] The present invention also provides a metallized film for a capacitor, which is obtained by using a preparation method according to any of the above technical solutions.
[0040] The present invention also provides a capacitor, characterized in that the capacitor comprises a metallized film for a capacitor obtained by the preparation method of any of the above technical solutions.
[0041] Beneficial Effects
[0042] The preparation method of the invention firstly adopts raw materials including 1,4-benzenedicarboxaldehyde, zirconium diboride and tetraethyl orthosilicate to prepare inorganic reinforcing materials; then adopts raw materials including 4,4'-diaminobiphenyl, triphenyl phosphate, ethylene-1-octene copolymer, polyethylene and polypropylene to prepare modified polypropylene materials; then melt-mixes, casts and biaxially stretches raw materials including polyvinyl alcohol, silane coupling agent, N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, inorganic reinforcing materials and modified polypropylene materials to obtain a base film; then applies a polyester coating on the base film, and successively irradiates the base film with an electron beam and an ultraviolet light source to obtain a modified base film; finally, vacuum evaporation forms a metal layer on one side of the modified base film having the polyester coating to obtain a metallized film.
[0043] In the above steps, zirconium diboride is a stable compound formed by boron and zirconium, which has the characteristics of high hardness, high melting point and high stability, and can be used to improve the high temperature resistance and mechanical strength of polypropylene-based films. Triphenyl phosphate is used to improve the flame retardancy and processability of polypropylene on the one hand, and to improve the compatibility of polypropylene with other materials on the other hand.
[0044] In order to solve the problem that the inorganic reinforcing material including zirconium diboride is easy to agglomerate in a polypropylene substrate, the present invention adds 1,4-benzenedicarboxaldehyde to the inorganic reinforcing material, adds 4,4'-diaminobiphenyl to the polypropylene material, and melt-mixes the inorganic reinforcing material and the modified polypropylene material with N-hydroxynaphthaleneimide trifluoromethanesulfonic acid. The sulfonate bond of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid breaks under ultraviolet light irradiation, generates acid and free radicals, and then catalyzes the condensation reaction of 1,4-benzenedicarboxaldehyde loaded on the inorganic reinforcing material and 4,4'-diaminobiphenyl in the polypropylene material, so that the inorganic reinforcing material and the polypropylene material are organically connected through the imide structure.
[0045] The imide structure can not only improve the heat resistance of polypropylene, but also enable the inorganic reinforcing material to be evenly and stably dispersed in the polymer through organic bonding by chemical bonds, thereby avoiding agglomeration. In summary, the metallized film obtained by the technical solution of the present invention has an inorganic reinforcing material that can be evenly and stably dispersed, has a good material homogeneity, good heat resistance, and excellent mechanical properties. DETAILED DESCRIPTION
[0046] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, a detailed description is given below in conjunction with specific embodiments of the present invention.
[0047] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0048] The present invention provides a method for preparing a metallized film for a capacitor, the preparation method comprising:
[0049] S100, preparing an inorganic reinforcing material using raw materials including 1,4-phthalaldehyde, zirconium diboride, and ethyl orthosilicate;
[0050] S200, preparing a modified polypropylene material using raw materials including 4,4'-diaminobiphenyl, triphenyl phosphate, ethylene-1-octene copolymer, polyethylene, and polypropylene;
[0051] S300, melt-mixing, casting and biaxially stretching raw materials including polyvinyl alcohol, silane coupling agent, N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, inorganic reinforcing material and modified polypropylene material to obtain a base film;
[0052] S400, applying a polyester coating on the base film, and irradiating the base film with an electron beam and an ultraviolet light source in sequence to obtain a modified base film;
[0053] S500, forming a metal layer by vacuum evaporation on the side of the modified base film having the polyester coating to obtain a metallized film.
[0054] The thickness of the modified base film is 5 μm to 20 μm, and the thickness of the metal layer is 5 nm to 50 nm.
[0055] In the above steps, the inorganic reinforcing material is used to improve the high temperature resistance and mechanical strength of polypropylene. Compared with other inorganic non-metallic nanopowder materials such as silicon oxide, zirconium oxide, and aluminum oxide, zirconium diboride not only has a higher hardness, but also has a higher melting point and thermal stability. Therefore, the above technical solution of the present invention uses zirconium diboride as one of the raw materials of the inorganic reinforcing material.
[0056] Triphenyl phosphate has flame retardancy and toughening effects, and can be used as a flame retardant and toughening agent in the preparation process of polymer materials. Compared with the technical solution of directly mixing triphenyl phosphate with a polymer, the present invention performs electron beam irradiation treatment on the polypropylene-based film after preparing the polypropylene-based film added with triphenyl phosphate. Triphenyl phosphate can induce a free radical polymerization reaction under the irradiation of an electron beam, so that the methyl group of the polypropylene side chain is grafted and modified, and converted into a polar covalent structure containing a phosphorus-oxygen double bond, thereby improving the flame retardancy and processability of polypropylene on the one hand, and improving the compatibility of polypropylene with other polymers on the other hand.
[0057] Since inorganic reinforcing materials are easy to agglomerate in polypropylene substrates, the present invention proposes a technical solution for organically combining inorganic reinforcing materials and polypropylene through chemical bonds. Specifically, the present invention adds 1,4-benzenedicarboxaldehyde to the inorganic reinforcing material and adds 4,4'-diaminobiphenyl to the polypropylene material, and then melt-mixes the inorganic reinforcing material and the modified polypropylene material with N-hydroxynaphthaleneimide trifluoromethanesulfonic acid. N-hydroxynaphthaleneimide trifluoromethanesulfonic acid is used as a photoacid catalyst, which will break the sulfonate bond under ultraviolet light irradiation and generate acid and free radicals. The acid and free radicals can catalyze and promote the condensation reaction of 1,4-benzenedicarboxaldehyde loaded on the inorganic reinforcing material and 4,4'-diaminobiphenyl in the polypropylene material.
[0058] Compared with the technical solution in the prior art of preparing polyamic acid by diamine and dianhydride, then imidizing the polyamic acid by high temperature treatment to obtain polyimide, and mixing it with inorganic powder and polypropylene, the present invention drives the aldehyde-ammine condensation reaction by ultraviolet irradiation and acid catalysis, so that the inorganic reinforcing material and the polypropylene material are organically connected through the imide structure. The imide structure can not only improve the heat resistance of polypropylene, but also enable the inorganic reinforcing material and polypropylene to be tightly connected through the -CO-NR-CO- structure of the imide, promote the uniform and stable dispersion of the inorganic reinforcing material, and avoid its agglomeration.
[0059] In addition, considering that the thermal stability of 1,4-benzenedicarboxaldehyde and N-hydroxynaphthaleneimide trifluoromethanesulfonic acid is not high, in order to prevent the two from decomposing during the melt mixing process, the present invention adds ethylene-1-octene copolymer and polyethylene to polypropylene to reduce the melt mixing temperature and protect 1,4-benzenedicarboxaldehyde and N-hydroxynaphthaleneimide trifluoromethanesulfonic acid.
[0060] In some implementations of the present invention, S100 specifically includes:
[0061] S110, dissolving 1,4-benzenedicaldehyde in ethanol at a mass ratio of 1,4-benzenedicaldehyde: zirconium diboride: ethyl orthosilicate: water: ethanol = (2-6): (10-20): (30-50): (30-50): 100, and then adding zirconium diboride, ethyl orthosilicate and water and mixing them evenly to obtain a first mixture;
[0062] S120, adjusting the pH value of the first mixture to 4 to 5 by dropwise adding aqueous hydrochloric acid solution and stirring, and continuing stirring for 2 h to 2.5 h to obtain silica sol;
[0063] S130, placing the silica sol in anhydrous ethanol and soaking it at a temperature of 50° C. to 55° C. for 30 to 36 hours to obtain a silica gel;
[0064] S140, drying the silicone gel at a temperature of 100° C. to 120° C. under normal pressure, and grinding the silica gel into powder to obtain an inorganic reinforcing material.
[0065] The purpose of the above steps is to achieve a thorough mixing of 1,4-benzenedicarboxaldehyde and an inorganic reinforcing material including zirconium diboride. Specifically, zirconium diboride is a nano-scale powder material, and its average particle size is preferably 1nm to 30nm. 1,4-benzenedicarboxaldehyde is soluble in ethanol. Ethyl orthosilicate is used as an organosilicon source. In a mixture of water and alcohol, it can be hydrolyzed with hydrochloric acid as a catalyst to form a silica sol mixed with 1,4-benzenedicarboxaldehyde and zirconium diboride particles. After the silica sol is immersed and aged in anhydrous ethanol, a silica gel can be formed. By drying the silica gel, a silicon oxide inorganic reinforcing material loaded with 1,4-benzenedicarboxaldehyde and zirconium diboride can be obtained.
[0066] It can be understood that the above steps prepare silicon oxide powder loaded with 1,4-benzenedicarboxaldehyde and zirconium diboride by the sol-gel method through the addition conditions of the raw materials. In the prior art, various methods such as supercritical drying and calcination can be used to achieve the conversion of silica gel into silicon oxide powder. However, considering that supercritical drying will extract 1,4-benzenedicarboxaldehyde and high-temperature calcination will cause thermal decomposition of 1,4-benzenedicarboxaldehyde, the present invention adopts atmospheric pressure drying to prepare silicon oxide inorganic reinforcement material. Among them, the temperature of atmospheric pressure drying is preferably 100°C to 120°C.
[0067] Compared with the method of directly mechanically mixing 1,4-benzenedicarboxaldehyde, zirconium diboride and silicon oxide, by using an organic silicon source, 1,4-benzenedicarboxaldehyde and zirconium diboride are added during the preparation of silicon oxide by the sol-gel method, and silicon oxide uniformly loaded with 1,4-benzenedicarboxaldehyde and zirconium diboride can be obtained. The above method helps zirconium diboride and silicon oxide to be closely linked with polypropylene through aldehyde-ammonia condensation.
[0068] In some implementations of the present invention, S200 specifically includes:
[0069] S210, weighing and mixing 4,4'-diaminobiphenyl, triphenyl phosphate, ethylene-1-octene copolymer, polyethylene and polypropylene in a mass ratio of 4,4'-diaminobiphenyl:triphenyl phosphate:ethylene-1-octene copolymer:polyethylene:polypropylene=(2-6):(2-6):(4-8):(10-20):100 to obtain a second mixture;
[0070] S220, sending the second mixture into an internal mixer, mixing at a temperature of 150° C. to 160° C. for 20 min to 40 min, discharging, cooling, and pelletizing to obtain a modified polypropylene material;
[0071] Among them, the weight average molecular weight of polyethylene is 200,000 to 300,000, and the weight average molecular weight of polypropylene is 200,000 to 250,000.
[0072] Polyethylene has excellent low temperature resistance and chemical stability, and its melting temperature is low. The introduction of ethylene-1-octene copolymer into polypropylene can interrupt the regularity of the polypropylene molecular chain, thereby reducing its crystallinity and melting point. This random copolymerization destroys the ordered structure of the molecular chain, weakens the interaction force between small molecules, increases the distance between molecules, and thus reduces the melting temperature of the material. Therefore, the above steps reduce the melt mixing temperature of polypropylene by adding ethylene-1-octene copolymer and polyethylene, thereby protecting 1,4-benzenedialdehyde and N-hydroxynaphthaleneimide trifluoromethanesulfonic acid. In addition, the selection of polyethylene and polypropylene with lower molecular weight can also help to further reduce the melting temperature.
[0073] In some implementations of the present invention, S300 specifically includes:
[0074] S310, weighing and mixing polyvinyl alcohol, silane coupling agent, N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, inorganic reinforcing material and modified polypropylene material according to a mass ratio of polyvinyl alcohol: silane coupling agent: N-hydroxynaphthaleneimide trifluoromethanesulfonic acid: inorganic reinforcing material: modified polypropylene material = (1-2): (2-4): (2-4): (10-15): 100 to obtain a third mixture;
[0075] S320, feeding the third mixture into a twin-screw extruder, and extruding the mixture after melt-mixing at a temperature of 170° C. to 190° C. to obtain a sheet-like fluid;
[0076] S330, casting the sheet-like fluid through a chilled roller at 80° C. to 100° C. and a high-pressure air knife to obtain a membrane;
[0077] S340, stretch the film in the longitudinal direction at a stretching ratio of 4 to 5 times and in the transverse direction at a stretching ratio of 5 to 6 times on a mechanical stretching machine at a temperature of 125°C to 145°C, and heat-set at a temperature of 150°C to 160°C to obtain a base film.
[0078] In the above steps, the silane coupling agent is preferably γ-aminopropyltriethoxysilane. It is understood that the twin-screw extruder has multiple heating zones, preferably 3 to 4. The temperature of each heating zone can be the same or there can be a gradient change. In general, the temperature range of melt mixing can be controlled at 170°C to 190°C.
[0079] The chilling roller can achieve rapid cooling of the melt sheet fluid through the convection of the heat dissipating liquid in its internal flow channel. The high-pressure air knife can use the high-pressure airflow to blow away the dust and impurities on the surface of the polymer, and accelerate the heat dissipation of the polymer through the high-pressure airflow, so as to obtain a cooled film. The film can be stretched into a polypropylene base film by biaxial stretching in the longitudinal and transverse directions.
[0080] Before vacuum evaporation of the polypropylene base film, the polypropylene base film needs to be treated. In the prior art, methods such as corona treatment and potassium permanganate immersion oxidation treatment are generally used to improve the wettability and roughness of the polypropylene base film, the bonding strength between the polypropylene base film and the metal coating, and the uniformity of the metal coating.
[0081] Corona treatment bombards the surface of polypropylene film with high-energy electrons or ions, causing the surface molecules to break and rearrange, thereby forming a large number of polar groups. During the corona treatment process, the plasma bombardment of the surface of the polypropylene film will also cause the surface to form an uneven rough surface. Polar groups can make it easier for the polypropylene film to form a strong chemical bond with the metal coating. The increase in roughness helps to improve the mechanical bite force between the metal coating and the base film. Therefore, corona treatment can improve the bonding strength between the polypropylene base film and the metal coating.
[0082] The principle of potassium permanganate immersion oxidation treatment is similar to that of corona treatment. It produces polar groups such as hydroxyl and carboxyl groups on the surface of polypropylene through oxidation treatment, thereby enhancing the interface bonding ability between the metal coating and the base film.
[0083] In some embodiments of the present invention, the pretreatment before vacuum evaporation of the polypropylene base film is performed by S400, and S400 includes:
[0084] S410, feeding butanediol and ethylene terephthalate into a vacuum reactor in a mass ratio of titanium dioxide: zinc acetate: butanediol: ethylene terephthalate = (1-2): (4-6): (50-60): 100, reacting at a temperature of 180° C. to 190° C. for 60 min to 100 min, adding titanium dioxide and zinc acetate, raising the temperature to 220° C. to 250° C. and continuing the reaction for 40 min to 60 min to obtain polyester;
[0085] S420, mixing polyester and carbon tetrachloride in a mass ratio of polyester: carbon tetrachloride = (20-30): 100, and heating to 65° C. to 70° C. to obtain a polyester coating;
[0086] S430, applying the polyester coating on the base film at a mass ratio of polyester coating: base film = (2-4): 100, and heating and drying to evaporate and remove carbon tetrachloride;
[0087] S440, successively irradiating the base film with an electron beam and an ultraviolet light source to obtain a modified base film; the radiation dose of the electron beam irradiation treatment is 20kGy-30kGy, and the exposure dose of the ultraviolet light source irradiation treatment is 1000mJ / cm 2 Up to 1200mJ / cm 2 .
[0088] In the above steps, under the catalytic action of zinc acetate, polyethylene terephthalate containing titanium dioxide can be obtained through the transesterification reaction of ethylene terephthalate and butanediol and further polycondensation reaction. Polyethylene terephthalate, as a polyester material, has more polar groups. The multiple polar functional groups it contains can form interaction points and new chemical bonds with titanium dioxide under the irradiation of ultraviolet light source, thereby improving its interface bonding ability with polypropylene material and metal coating respectively. Specifically, when titanium dioxide is exposed to ultraviolet light, it will excite electrons to jump from the valence band to the conduction band, forming conduction band electrons, while leaving holes in the valence band. The conduction band electrons have higher energy and mobility, and can interact with the positively charged part in the polar group to form electron transfer or electron capture. The valence band holes can interact with the negatively charged part in the polar group to form hole capture or hole transfer. Therefore, under the irradiation of ultraviolet light source, the polyester coating containing titanium dioxide can improve the interface bonding ability between the polypropylene base film and the metal coating by forming chemical bonds.
[0089] In the present invention, a metal layer is formed by vacuum evaporation on the side of the modified base film having the polyester coating to obtain a metallized film through S500. It should be noted that vacuum evaporation is a relatively mature prior art, and those skilled in the art can select and adjust the process parameters of vacuum evaporation according to actual needs. Preferably, in S500, the conditions for vacuum evaporation include: the evaporation material is aluminum, the vacuum degree is 2×10 -5 Pa or less, the evaporation rate is 0.02A / s to 0.08A / s, the evaporation time is 60s to 180s, and the substrate temperature is 140°C to 150°C.
[0090] Embodiment 1
[0091] This embodiment prepares a metallized film for capacitors, and the specific process is as follows:
[0092] S1. Dissolve 1,4-benzenedicaldehyde in ethanol in a mass ratio of 1,4-benzenedicaldehyde: zirconium diboride: ethyl orthosilicate: deionized water: ethanol = 5:10:30:35:100, add zirconium diboride and stir evenly, continue to add ethyl orthosilicate and deionized water, and mix evenly with ultrasound to obtain a first mixture in the form of a suspension; add a 36% hydrochloric acid aqueous solution to the first mixture and stir until the pH value of the first mixture is adjusted to 4, and then continue to stir slowly for 2 hours to obtain silica sol; place the silica sol in anhydrous ethanol, soak it at a temperature of 50°C for 30 hours, replace the anhydrous ethanol every 6 hours, and take out the silica gel after the time is up; wash the silica gel, dry it at normal pressure at a temperature of 110°C, grind it, and obtain a powdered inorganic reinforcing material;
[0093] S2. According to the mass ratio of 4,4'-diaminobiphenyl: triphenyl phosphate: ethylene-1-octene copolymer: polyethylene: polypropylene = 4:4:6:20:100, 4,4'-diaminobiphenyl, triphenyl phosphate, ethylene-1-octene copolymer, polyethylene with a weight average molecular weight of 200,000 to 300,000, and polypropylene with a weight average molecular weight of 200,000 to 250,000 are weighed and mixed to obtain a second mixture; the second mixture is sent to an internal mixer, and is internally mixed at a temperature of 150° C. for 20 minutes. After the material is discharged, it is cooled to room temperature and pelletized into particles of 0.5 mm to 0.8 mm to obtain a modified polypropylene material;
[0094] S3. According to the mass ratio of polyvinyl alcohol: γ-aminopropyl triethoxysilane: N-hydroxynaphthalimide trifluoromethanesulfonic acid: inorganic reinforcing material: modified polypropylene material = 2:2:2:10:100, polyvinyl alcohol, γ-aminopropyl triethoxysilane, N-hydroxynaphthalimide trifluoromethanesulfonic acid, the inorganic reinforcing material obtained in S1 and the modified polypropylene material obtained in S2 are weighed and mixed to obtain a third mixture; the third mixture is fed into a twin-screw extruder and sequentially passed through various temperature intervals, the first temperature interval being 170°C to 175°C, the second temperature interval being 175°C to 180°C, and ... ℃, the third temperature range is 180℃ to 190℃, and after melt mixing, extrusion is performed to obtain a sheet fluid; the sheet fluid is cast through a 90℃ chilled roller and a 90℃ high-pressure air knife to obtain a membrane; the membrane is longitudinally stretched with a stretching ratio of 4 times on a mechanical stretching machine, the preheating temperature is 125℃ to 130℃, the stretching temperature is 140℃ to 145℃, and then the stretching ratio is 6 times. The transverse stretching, the preheating temperature is 125℃ to 130℃, the stretching temperature is 140℃ to 145℃, and finally heat-set at a temperature of 150℃ to 160℃ to obtain a base film;
[0095] S4. According to the mass ratio of titanium dioxide: zinc acetate: butanediol: ethylene terephthalate = 2:4:50:100, butanediol and ethylene terephthalate are fed into a vacuum reactor, reacted at 180°C for 60 minutes, titanium dioxide and zinc acetate are added, and the temperature is raised to 220°C and the reaction is continued for 40 minutes to obtain polyester; according to the mass ratio of polyester: carbon tetrachloride = 20:100, polyester and carbon tetrachloride are mixed, and heated to 70°C to obtain polyester coating; according to the mass ratio of polyester coating: base film = 4:100, the polyester coating is applied on the base film, and heated and dried to evaporate and remove carbon tetrachloride;
[0096] S5. First, the base film coated with the polyester coating is irradiated with an electron beam at a radiation dose of 20 kGy-30 kGy, and then a 1500 W ultraviolet light source is used to irradiate the base film coated with the polyester coating with ultraviolet light, and the exposure dose is 1000 mJ / cm 2Up to 1200mJ / cm 2 ;
[0097] S6. After the irradiation, vacuum evaporation is performed on the side of the modified base film with the polyester coating to form an aluminum layer, and finally a metallized film is obtained. The conditions of the vacuum evaporation include: the vacuum degree does not exceed 2×10 -5 Pa, the evaporation rate is 0.05 A / s, the evaporation time is 150 s, the substrate temperature is 140 °C, the wire feeding speed is 600 mm / min, and the evaporation boat temperature is 660 °C.
[0098] Embodiment 2
[0099] This embodiment prepares a metallized film for capacitors, and the specific process is as follows:
[0100] S1. According to the mass ratio of zirconium diboride:ethyl orthosilicate:deionized water:ethanol = 10:30:35:100, zirconium diboride, ethyl orthosilicate, ethanol and deionized water are ultrasonically mixed to obtain a first mixture in the form of a suspension; a 36% hydrochloric acid aqueous solution is added dropwise to the first mixture and stirred until the pH value of the first mixture is adjusted to 4, and then the reaction is slowly stirred for 2 hours to obtain a silica sol; the silica sol is placed in anhydrous ethanol and soaked at 50°C for 30 hours, and the anhydrous ethanol is replaced every 6 hours. After the time is up, the silica gel is taken out; the silica gel is washed and dried at 110°C under normal pressure, and ground to obtain a powdered inorganic reinforcing material;
[0101] S2. According to the mass ratio of triphenyl phosphate:ethylene-1-octene copolymer:polyethylene:polypropylene=4:6:20:100, triphenyl phosphate, ethylene-1-octene copolymer, polyethylene with a weight average molecular weight of 200,000 to 300,000, and polypropylene with a weight average molecular weight of 200,000 to 250,000 are weighed and mixed to obtain a second mixture; the second mixture is sent to an internal mixer, and is internally mixed at a temperature of 150° C. for 20 minutes. After the material is discharged, it is cooled to room temperature and pelletized into particles of 0.5 mm to 0.8 mm to obtain a modified polypropylene material;
[0102] S3. According to the mass ratio of polyvinyl alcohol:γ-aminopropyltriethoxysilane:inorganic reinforcing material:modified polypropylene material=2:2:10:100, polyvinyl alcohol, γ-aminopropyltriethoxysilane, the inorganic reinforcing material obtained in S1 and the modified polypropylene material obtained in S2 are weighed and mixed to obtain a third mixture; the third mixture is fed into a twin-screw extruder and sequentially passed through various temperature intervals, the first temperature interval is 170°C to 175°C, the second temperature interval is 175°C to 180°C, and the third temperature interval is 180°C to 1 90°C, melt-mixed and extruded to obtain a sheet fluid; the sheet fluid was cast through a 90°C chilled roller and a 90°C high-pressure air knife to obtain a film; the film was longitudinally stretched with a stretching ratio of 4 times on a mechanical stretching machine, the preheating temperature was 125°C to 130°C, the stretching temperature was 140°C to 145°C, and then the stretching ratio was 6 times the transverse stretching, the preheating temperature was 125°C to 130°C, the stretching temperature was 140°C to 145°C, and finally heat-set at a temperature of 150°C to 160°C to obtain a base film;
[0103] S4. According to the mass ratio of titanium dioxide: zinc acetate: butanediol: ethylene terephthalate = 2:4:50:100, butanediol and ethylene terephthalate are fed into a vacuum reactor, reacted at 180°C for 60 minutes, titanium dioxide and zinc acetate are added, and the temperature is raised to 220°C and the reaction is continued for 40 minutes to obtain polyester; according to the mass ratio of polyester: carbon tetrachloride = 20:100, polyester and carbon tetrachloride are mixed, and heated to 70°C to obtain polyester coating; according to the mass ratio of polyester coating: base film = 4:100, the polyester coating is applied on the base film, and heated and dried to evaporate and remove carbon tetrachloride;
[0104] S5. First, the base film coated with the polyester coating is irradiated with an electron beam at a radiation dose of 20 kGy-30 kGy, and then a 1500 W ultraviolet light source is used to irradiate the base film coated with the polyester coating with ultraviolet light, and the exposure dose is 1000 mJ / cm 2 Up to 1200mJ / cm 2 ;
[0105] S6. After the irradiation, vacuum evaporation is performed on the side of the modified base film with the polyester coating to form an aluminum layer, and finally a metallized film is obtained. The conditions of the vacuum evaporation include: the vacuum degree does not exceed 2×10 -5 Pa, the evaporation rate is 0.05 A / s, the evaporation time is 150 s, and the substrate temperature is 140 °C.
[0106] Embodiment 3
[0107] This embodiment prepares a metallized film for capacitors, and the specific process is as follows:
[0108] S1. According to the mass ratio of zirconium diboride:ethyl orthosilicate:deionized water:ethanol = 10:30:35:100, zirconium diboride, ethyl orthosilicate, ethanol and deionized water are ultrasonically mixed to obtain a first mixture in the form of a suspension; a 36% hydrochloric acid aqueous solution is added dropwise to the first mixture and stirred until the pH value of the first mixture is adjusted to 4, and then the reaction is slowly stirred for 2 hours to obtain a silica sol; the silica sol is placed in anhydrous ethanol and soaked at 50°C for 30 hours, and the anhydrous ethanol is replaced every 6 hours. After the time is up, the silica gel is taken out; the silica gel is washed and dried at 110°C under normal pressure, and ground to obtain a powdered inorganic reinforcing material;
[0109] S2. According to the mass ratio of triphenyl phosphate:ethylene-1-octene copolymer:polyethylene:polypropylene=4:6:20:100, triphenyl phosphate, ethylene-1-octene copolymer, polyethylene with a weight average molecular weight of 200,000 to 300,000, and polypropylene with a weight average molecular weight of 200,000 to 250,000 are weighed and mixed to obtain a second mixture; the second mixture is sent to an internal mixer, and is internally mixed at a temperature of 150° C. for 20 minutes. After the material is discharged, it is cooled to room temperature and pelletized into particles of 0.5 mm to 0.8 mm to obtain a modified polypropylene material;
[0110] S3. According to the mass ratio of polyvinyl alcohol:γ-aminopropyltriethoxysilane:inorganic reinforcing material:modified polypropylene material=2:2:10:100, polyvinyl alcohol, γ-aminopropyltriethoxysilane, the inorganic reinforcing material obtained in S1 and the modified polypropylene material obtained in S2 are weighed and mixed to obtain a third mixture; the third mixture is fed into a twin-screw extruder and sequentially passed through various temperature intervals, the first temperature interval is 170°C to 175°C, the second temperature interval is 175°C to 180°C, and the third temperature interval is 180°C to 1 90°C, melt-mixed and extruded to obtain a sheet fluid; the sheet fluid was cast through a 90°C chilled roller and a 90°C high-pressure air knife to obtain a film; the film was longitudinally stretched with a stretching ratio of 4 times on a mechanical stretching machine, the preheating temperature was 125°C to 130°C, the stretching temperature was 140°C to 145°C, and then the stretching ratio was 6 times the transverse stretching, the preheating temperature was 125°C to 130°C, the stretching temperature was 140°C to 145°C, and finally heat-set at a temperature of 150°C to 160°C to obtain a base film;
[0111] S4, irradiating the basement membrane with an electron beam at a radiation dose of 20 kGy-30 kGy;
[0112] S6. After the irradiation, an aluminum layer is formed on the base film by vacuum evaporation to finally obtain a metallized film. The conditions for vacuum evaporation include: the vacuum degree does not exceed 2×10 -5Pa, the evaporation rate is 0.05 A / s, the evaporation time is 150 s, and the substrate temperature is 140 °C.
[0113] Performance parameters
[0114] Table 1 lists the performance parameters of the metallized films of Examples 1 to 3. Among them, the conditions of the accelerated aging test are to place it under environmental conditions of a temperature of 90°C and a relative humidity of 90% for 10 days. According to Table 1, the metallized film obtained in Example 1 has better heat resistance and is resistant to aging, and the performance parameters after the accelerated aging test change little. The metallized film obtained in Example 3 is slightly better than that in Example 2 in terms of longitudinal heat shrinkage, which may be due to the fact that Example 3 is not coated with a polyester base film. Regarding other performance parameters such as heat resistance temperature and breakdown strength, Example 2 is better than Example 3. The performance of Example 1 in all aspects is significantly better than the other two examples, which shows that the chemical bonding of imide caused by ultraviolet radiation and the effect of polar groups in polyester and titanium dioxide improve the performance of the metallized film.
[0115] Table 1
[0116]
[0117] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing a metallized film for a capacitor, characterized in that: The preparation method comprises: S100, preparing an inorganic reinforcing material using raw materials including 1,4-phthalaldehyde, zirconium diboride, and ethyl orthosilicate; S200, preparing a modified polypropylene material using raw materials including 4,4'-diaminobiphenyl, triphenyl phosphate, ethylene-1-octene copolymer, polyethylene, and polypropylene; S300, melt-mixing, casting and biaxially stretching raw materials including polyvinyl alcohol, silane coupling agent, N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, the inorganic reinforcing material and the modified polypropylene material to obtain a base film; S400, applying a polyester coating on the base film, and irradiating the base film with an electron beam and an ultraviolet light source in sequence to obtain a modified base film; S500, forming a metal layer by vacuum evaporation on the side of the modified base film having the polyester coating to obtain the metallized film; S100 specifically includes: S110, dissolving the 1,4-benzenedicarboxaldehyde in the ethanol according to a mass ratio of 1,4-benzenedicarboxaldehyde: zirconium diboride: ethyl orthosilicate: water: ethanol = (2-6): (10-20): (30-50): (30-50): 100, and then adding the zirconium diboride, the ethyl orthosilicate and the water and mixing them evenly to obtain a first mixture; S120, adjusting the pH value of the first mixture to 4 to 5 by dropwise adding a hydrochloric acid aqueous solution and stirring, and continuing stirring for 2 h to 2.5 h to obtain a silica sol; S130, placing the silica sol in anhydrous ethanol and soaking it at a temperature of 50° C. to 55° C. for 30 to 36 hours to obtain a silica gel; S140, drying the silicone gel at a temperature of 100° C. to 120° C. under normal pressure, and grinding the silicone gel into powder to obtain the inorganic reinforcing material; S200 specifically includes: S210, weighing and mixing the 4,4'-diaminobiphenyl, the triphenyl phosphate, the ethylene-1-octene copolymer, the polyethylene and the polypropylene in a mass ratio of 4,4'-diaminobiphenyl:triphenyl phosphate:ethylene-1-octene copolymer:polyethylene:polypropylene=(2-6):(2-6):(4-8):(10-20):100 to obtain a second mixture; S220, sending the second mixture into an internal mixer, mixing at a temperature of 150° C. to 160° C. for 20 min to 40 min, discharging, cooling, and pelletizing to obtain the modified polypropylene material; S400 includes: S410, feeding the butanediol and the ethylene terephthalate into a vacuum reactor in a mass ratio of titanium dioxide: zinc acetate: butanediol: ethylene terephthalate = (1-2): (4-6): (50-60): 100, reacting at a temperature of 180° C. to 190° C. for 60 min to 100 min, adding the titanium dioxide and the zinc acetate, raising the temperature to 220° C. to 250° C. and continuing the reaction for 40 min to 60 min to obtain polyester; S420, mixing the polyester and the carbon tetrachloride at a mass ratio of polyester: carbon tetrachloride = (20-30): 100, and heating to 65° C. to 70° C. to obtain a polyester coating; S430, applying the polyester coating onto the base film at a mass ratio of polyester coating: base film = (2-4): 100, and heating and drying to evaporate and remove the carbon tetrachloride; S440, successively using an electron beam and an ultraviolet light source to perform the irradiation treatment on the base film to obtain the modified base film.
2. The preparation method according to claim 1, characterized in that: The weight average molecular weight of the polyethylene is 200,000 to 300,000, and the weight average molecular weight of the polypropylene is 200,000 to 250,000.
3. The preparation method according to claim 2, characterized in that: S300 specifically includes: S310, weighing and mixing the polyvinyl alcohol, the silane coupling agent, the N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, the inorganic reinforcing material and the modified polypropylene material in a mass ratio of polyvinyl alcohol: silane coupling agent: N-hydroxynaphthaleneimide trifluoromethanesulfonic acid: inorganic reinforcing material: modified polypropylene material = (1-2): (2-4): (2-4): (10-15): 100 to obtain a third mixture; S320, feeding the third mixture into a twin-screw extruder, and extruding the mixture after melt-kneading at a temperature of 170° C. to 190° C. to obtain a sheet-like fluid; S330, casting the sheet-like fluid through a chilled roller at 80° C. to 100° C. and a high-pressure air knife to obtain a membrane; S340, stretching the film in the longitudinal direction at a stretching ratio of 4 to 5 times and in the transverse direction at a stretching ratio of 5 to 6 times on a mechanical stretching machine at a temperature of 125°C to 145°C, and heat-setting at a temperature of 150°C to 160°C to obtain the base film.
4. The preparation method according to claim 1, characterized in that: In S440, the radiation dose of the irradiation treatment using an electron beam is 20 kGy-30 kGy, and the exposure dose of the irradiation treatment using an ultraviolet light source is 1000 mJ / cm 2 Up to 1200mJ / cm 2 .
5. The preparation method according to any one of claims 1 to 3, characterized in that: In S500, the vacuum evaporation conditions include: the evaporation material is aluminum, the vacuum degree is 2×10 -5 Pa or less, the evaporation rate is 0.02A / s to 0.08A / s, the evaporation time is 60s to 180s, and the substrate temperature is 140°C to 150°C.
6. The preparation method according to any one of claims 1 to 3, characterized in that: The modified base film has a thickness of 5 mm to 20 mm, and the metal layer has a thickness of 5 nm to 50 nm.
7. A metallized film for a capacitor, characterized in that: The metallized film for capacitor is obtained by the preparation method according to any one of claims 1 to 6.
8. A capacitor, characterized in that: The capacitor comprises a metallized film for a capacitor obtained by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Ultra-thin heat-resistant bidirectional synchronous stretching special material and preparation method
CN118271780B
Photoresist and patterning method of imine material
CN111880371A
Ultrathin temperature-resistant bidirectional synchronous stretching special material and preparation method thereof
CN117362894A